An Introduction to the Works of J. M. Coetzee: Exploring Coetzee's Unimaginable Portrayal of Societal Issues (Journal of Advances and Scholarly Researches in Allied Education, 2017)
J. M. Coetzee is one of the youthful, dissident literary voices speaking against the apartheid regime in the 1970’s and 1980’s. Coetzee’s distinctive prose was identified early as both elusive and as politically urgent. His work has been compared favorably with Nabokov, Kafka and Conrad. Most of Coetzee’s Writings reflect either directly or indirectly on recent events unfolding within South African society, although critics have warned against straightforward allegorical readings of his work. This paper focuses on how Coetzee has problematized issues of writing, authority, power, race, patriarchy, gender, marginality, voice among others including authorial identity in unimaginable ways in his novels.